Associations between zircon and Fe–Ti oxides in Hiltaba event magmatic rocks, South Australia: atomic- or pluton-scale processes?. Issue 2 (17th February 2020) - Ferguson, M. R. M.; Ehrig, K.; Meffre, S.; Cherry, A. R.
Abstract: The Hiltaba Suite intrusive rocks and penecontemporaneous Gawler Range Volcanics (GRV) comprise the 1590 Ma Gawler silicic large igneous province in the Gawler Craton, South Australia. Zircon is principally associated with Fe–Ti oxides and clusters of touching crystals in these rocks, including in the Roxby Downs Granite (RDG), host of the Olympic Dam iron oxide–copper–gold deposit, and in other intrusive rocks that comprise the Olympic Province. There has been no explicit evaluation and explanation of potential origins published for concentrations of zircon with Fe–Ti oxides (herein zircon-rich clusters) found in these and similar rocks of western North America and elsewhere. Here we use U–Pb geochronology, mineral morphologies and compositions, and insights from surface chemistry and liquid-bound particle interaction studies to investigate zircon-rich clusters and provide a model for their formation. U–Pb geochronology does not reveal any concordant zircon populations older than ca 1590 Ma, so it is unlikely that there are significant xenocrystic zircon grains or that the zircons include significant inherited cores. The lack of pre-magmatic zircon, consistent intra-grain and inter-grain zircon compositional trends, the predominance of oscillatory zoned zircon with morphologies indicating growth from hot, evolved silicate melts, and the lack of evidence for zircon recrystallisation, indicates that zircon crystallised in the host GRV and RDG magmas. Variable zircon compositions within individual clusters does not support epitaxial nucleation of zircon on Fe–Ti oxides, but it is likely that some zircon grains grew from seed crystals formed by exsolution of Zr from Fe–Ti oxides. Aggregation of isolated, liquid-bound crystals is energetically favourable, and the grainsize discrepancy between larger crystals (Fe–Ti oxides, pyroxenes) and smaller accessory minerals (zircon, apatite) maximises the disparity in particle velocities and hence enhances the opportunities for collisions and adhesion between these crystals. We propose that zircon adheres to Fe–Ti oxides with greater ease and/or with greater bond strengths, than to other phases present in the parental magmas. It is possible that this association is related to interactions between zircon and Fe–Ti oxide surface sites with opposing charges, presuming the distance between phase surfaces is sufficiently small. The occurrence of small zircon grains within Fe–Ti oxides and both euhedral zircon and zircon with asymmetric growth zonation in contact with Fe–Ti oxides indicates that several processes are responsible for the high concentrations of zircon crystals in some Fe–Ti oxide clusters. Zircon is principally associated with Fe--Ti oxides in 1.59 Ga Gawler Range Volcanics (GRV) and Roxby Downs Granite (RDG) U–Pb geochronology does not reveal any concordant zircon populations older than ca 1590 Ma Zircon compositions and morphologies indicate that zircon crystallised in the host RDG and GRV magmas and suggest recharge, reheating and mixing occurred in these magmatic systems Seed crystals, aggregation and surface chemical affinities contributed to the strong association of zircon and Fe–Ti oxides